Associations of multiple exposures to persistent toxic substances with the risk of hyperuricemia and subclinical uric acid levels in BIOAMBIENT.ES study. (February 2019) - Arrebola, Juan Pedro; Ramos, Juan José; Bartolomé, Mónica; Esteban, Marta; Huetos, Olga; Cañas, Ana I.; López-Herranz, Ana; Calvo, Eva; Pérez-Gómez, Beatriz; Castaño, Argelia; ,
Abstract: Hyperuricemia is becoming a serious public health issue, which is highly influenced by environmental factors, although there is still controversial information on the potential influence of the exposure to Persistent Toxic Substances (PTSs) in the general population. In this study we aimed to assess the association. PTS exposure with uric acid homeostasis in a sample of the Spanish population. Participants were recruited during 2009–2010 in all the main geographical areas of Spain. Exposure to 34 PTSs was estimated by chemical analyses of serum levels of 6 Polychlorinated Biphenyls (PCBs, n = 950), 13 Organochlorine Pesticides (OCPs, n = 453), 6 Perfluoroalkyl Substances (PFAs, n = 755), 7 Polybrominated Diphenyl Ethers (PBDEs, n = 365), urinary Cadmium (n = 926), and Lead in whole blood (n = 882). The two study outcomes were defined as the prevalence of hyperuricemia in the study population and uric acid levels, the latter only in individuals with no previous diagnosis of hyperuricemia. Statistical analyses were performed by means of binomial logistic regression and linear regression, and mixture effects were screened using Weighted Quantile Sum Regression (WQS). Serum concentrations of γ-HCH, o, p´- DDE, PCB-138, PCB-153, PFOA, and urinary Cadmium were associated with an increased risk of hyperuricemia, while PBDE-153 showed an inverse association with the effect. Furthermore, exposure to Cadmium, PCB-138, and to PCB-153 was positively associated with uric acid levels. Results were consistent after lipid adjustment or standardization. WQS analyses revealed a major contribution of PCB-153 within the PCB mixture on both the risk of hyperuricemia and uric acid levels. Sensitivity analyses were performed by adjusting for dietary habits, fasting glucose and estimated glomerular filtration rate. Overall, we found novel associations between human exposure to mixtures of PTSs and disturbances in uric acid homeostasis. However, we cannot completely rule out potential residual confounding effect or reversed-causality related to the cross-sectional design. Highlights: We assessed the contribution of PTSs on uric acid homeostasis in Spanish population. Concentrations of 34 PTSs were analyzed in serum or urine. PCB-138, PCB-153, PFOA, and Cadmium were positively associated with hyperuricemia. Cadmium, PCB-138, and PCB-153 were positively associated with uric acid levels. WQS analyses revealed a major effect of PCB-153 within the PCB mixture.